Characterization of New Cellulose Fiber Extracted from Pithecellobium dulce Tree - Sathishkumar, Tottyeapalayam Palanisamy; Navaneethakrishnan, Palanisamy; Shivaram, Subbaraya Velumani; Kanna, Sridhar Santhosh; Rajeshkumar, Lakshminarasimhan; Rajeshkumar, Guruswamy (Applied Science and Engineering Progress, 2023)
Lightweight materials are continuously required for various parts of automobile and aerospace applications. In this connection, natural fibers are widely used to develop polymer composites due to their being biodegradable and lightweight. The demand for natural fiber for developing the lightweight polymer composite is needed for new fibers. The present work extracts and characterizes the bio-fiber from the Pithecellobium dulce (PDs) plant. The Pithecellobium dulce fiber (PDF) has a cellulose content of 63.45 wt.%, hemicellulose content of 14.56 wt.%, lignin content of 8.45 wt.%, wax content of 0.37 wt.%, moisture content of 11.71 wt.%, and ash content of 4.85 wt.%. The physical density and crystallinity index of PDF was 1097 kg/m3 and 9.7 %. The tensile strength and Young’s modulus properties were identified as 317–1608 MPa and 8.41– 69.61 GPa. The thermal stability of PDF showed at higher temperatures of 339.1°C. This revealed higher cellulose content leading to the higher bonding of cellulose structure. The properties of PDFs can be used to make green polymer composites.